Pleioblatus simonii (carriere) Nakai-a Bamboo New to India from Arunachal Pradesh - Naithani, B. B.; Bennet, S. S. R. (Indian Forester, 1986)
Pleioblatus simonii (Carriere) Nakai, a bamboo native of China and Japan, is being reported for the first time from India based on a collection of the authors from Arunachal Pradesh.